Biomass and Carbon Stock Assessment in Agroforestry Practices: A Study in Southern Transition zone of Karnataka, India - Mehta, Mitali; Devagiri, G. M.; Satish, B. N.; Nayak, B. G.; Ravikumar, D.; Moran, Ankush (Indian Forester, 2025)
Agroforestry plays an important role in global carbon cycle and regulating the earth’s climate. The present study was conducted with the objective to know about the carbon sequestration potential of different agroforestry practices in Periyapatana and Hunsur tehsils of Mysore district, Karnataka. Based on the reconnaissance survey four prominent practices viz; multipurpose trees (MPT’s) on farmlands, block plantations, boundary plantations and control (i.e. agricultural crop without trees) were selected for the present study. Among the four practices, highest biomass, biomass carbon, soil organic carbon stock, total carbon was recorded in block plantations whereas lowest was recorded in control. Total biomass and biomass carbon varied from 3.92 Mg ha-1 to 63.39 Mg ha-1, 1.84 Mg ha-1 to 29.79 Mg ha-1, respectively. The SOC stock ranged from 13.14 to 22.05 Mg ha-1. Total carbon stock across the different practices ranged from 14.98 Mg ha-1 to 51.84 Mg ha-1. Thus, the study highlights the need for policies that promote agroforestry adoption through incentives, technical assistance and integration into national carbon offset programs, thereby reinforcing its potential as a nature-based solution for environmental sustainability and rural livelihoods.